2008
DOI: 10.4103/0971-3026.43846
|View full text |Cite
|
Sign up to set email alerts
|

Role of cervical ultrasonography in primary hyperparathyroidism

Abstract: Aim:To evaluate the role of USG in the preoperative localization of parathyroid adenomas in patients with symptomatic hyperparathyroidism and to compare its usefulness with that of scintigraphy scan and postoperative findings.Material and methods:Twenty-five patients with symptomatic primary hyperparathyroidism were subjected to USG of the neck and nuclear scintigraphy, followed by surgery. The results were independently analyzed and compared with per-operative findings.Results:The 25 patients had a total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…In all studies, diagnosis was confirmed by successful surgical removal of parathyroid pathology with or without post surgical follow up histology and blood assays. Five studies additionally confirmed surgical success with follow up assays (Bhansali et al 2006;Carlier et al 2008;Lo et al 2007;Prasannan et al 2007;Shaheen et al 2008), and three studies confirmed the nature of the excised lesion(s) with histology (Mihai et al 2006;Lo et al 2007;Carlier et al 2008). …”
Section: Medline Via Ovidspmentioning
confidence: 78%
See 4 more Smart Citations
“…In all studies, diagnosis was confirmed by successful surgical removal of parathyroid pathology with or without post surgical follow up histology and blood assays. Five studies additionally confirmed surgical success with follow up assays (Bhansali et al 2006;Carlier et al 2008;Lo et al 2007;Prasannan et al 2007;Shaheen et al 2008), and three studies confirmed the nature of the excised lesion(s) with histology (Mihai et al 2006;Lo et al 2007;Carlier et al 2008). …”
Section: Medline Via Ovidspmentioning
confidence: 78%
“…US was performed by experienced radiologists in two studies (Carlier et al 200;Lo et al 2007), experienced sonographers in two studies (Bhansali et al 2006;Sugg et al 2004), a parathyroid surgeon in one study (Prasannan et al 2007) and the operator was not specified by Mihai et al (2006) or Shaheen et al (2008). Two studies (Lo et al 2007;Shaheen et al 2008) indicated that multiple operators were involved in performing the ultrasound examinations in their studies.…”
Section: Study and Subject Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations